The limits of altruism in democratic Athens - Christ, Matthew Robert (Cambridge University Press, 2012)
"The Philanthropic Athenian? Athenians in the classical period (508-322 BC) were drawn to an image of themselves as a compassionate and generous people, who rushed to the aid of others in distress at home and abroad. Litigants in the popular courts appeal to this ideal when they call upon large panels of jurors collectively to intervene and help them against their unjust opponents with a favorable verdict. Speakers delivering funeral orations for the state's war dead portray Athenians as valiant rescuers of their Greek neighbors from mythical times on. Tragedians bring on stage mythical instances of Athenians helping desperate suppliants from other states. Orators addressing the Assembly sometimes invoke this tradition of helping others when urging their audiences to vote in favor of intervention abroad. In light of how prominently this heroic image of Athenians as noble helpers figures in public discourse, we can have little doubt that this was a central element of civic ideology. It is reasonable to ask, however, what relation this image bears to actual Athenian behavior at home and abroad and to what extent it simplifies or distorts Athenian attitudes toward helping others. This study focuses on how helping figured in Athenians' relations with their fellow citizens, their city, and other Greek city-states rather than on the role of helping in the more intimate relationships of family members and friends. The latter subject has drawn considerable scholarly attention in recent decades in work on the Athenian family and friendship, and there is a general consensus that Athenians, like other Greeks, were under strong pressure to help their family members and friends"--